Biomakers of toluene and the Impact Of exposure to toluene in Indoor Air on Public Health: Literature Review - Winata, Vina Pandi Ananta; Taufik Ikhtiar, Erwan; Wulandari, Ayu; Azizah, R.; Keman, Soedjajadi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Toluene is an organic solvent that is widely used in industry which is volatile and toxic to health. Based on data from the International Labor Organization in 2018, it is known that more than 1.8 million work-related deaths, one of which is due to toluene exposure, occur each year in Asia and the Pacific. Biomarker to determine the presence of toluene exposure in the human body, namely hippuric acid in the urine. This research is literature review. Database used in this study includes Science Direct and Google Scholar. There were several articles annotate that hippuric acid is a biomarker of toluene in human urine. Health problems due to exposure to toluene occur in humans who directly contact with glue and paint. Workers in gluing and coloring field had higher risk than workers in other field (P<0.01). Hippuric acid levels in the urine of workers exposed to toluene and xylene were 0.15 ± 0.04; 0.11 ± 0.01; and 0.19 ± 0.07 g g-1 creatinine, respectively. It is concluded that hippuric acid is a biomarker of toluene in human urine and the health effects due to exposure to toluene in indoor air include dizziness, vertigo, and eye irritation.